An analytical reading of the problems of studying and teaching modern and contemporary European history in Iraqi universitiesIbn Rushd College of Education is a model - Nagham Salam Ibraheem , Prof .Dr. (lark, 2024)
The issue of interest in the subject of Modern and Contemporary European History has become important for developing the creativity of the university student specializing in historical studies, in the form that he believes is the ability to employ the information he is exposed to, and  between its events in  scientific and logical manner that enriches him with knowledge and enhances his ability to absorb it at the appropriate time, and in accordance with this. We had to gradually re-study the classes, and we made us reconsider it based on the changes and mechanical modernity on the scene on the one hand, and what came to us from management sources, along with education and web translators, in a way that made the student able to use what he learned to understand contemporary historical events within a scientific and logical method.
Keywords: European history, the Cold War, contemporary, modernization